2022
DOI: 10.3390/antiox11101870
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Emergence of Psychosis

Abstract: Treatment and prevention strategies for schizophrenia require knowledge about the mechanisms involved in the psychotic transition. Increasing evidence suggests a redox imbalance in schizophrenia patients. This narrative review presents an overview of the scientific literature regarding blood oxidative stress markers’ evolution in the early stages of psychosis and chronic patients. Studies investigating peripheral levels of oxidative stress in schizophrenia patients, first episode of psychosis or UHR individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 128 publications
0
9
0
Order By: Relevance
“…Pregnancy is strongly linked to OS, especially under pathological conditions [39]. Recent works have shown that patients with a first episode of psychosis show a reduced antioxidant status along with a marked increase in oxidative markers [22,40]. The environment in which the mother lives exposes the placental tissue to a set of chemical, physical and biological agents of OS, which may have pathological consequences in this organ [41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pregnancy is strongly linked to OS, especially under pathological conditions [39]. Recent works have shown that patients with a first episode of psychosis show a reduced antioxidant status along with a marked increase in oxidative markers [22,40]. The environment in which the mother lives exposes the placental tissue to a set of chemical, physical and biological agents of OS, which may have pathological consequences in this organ [41].…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria were: meeting the diagnostic criteria for another Axis-I mental disorder or intellectual disability; or a history of neurodevelopmental disorders or head injury with loss of consciousness. The median age in the FE-PW group was 33.5 years, and the median gestational age was 40 (38)(39)(40)(41) weeks. For HC-PW, the median age was 33.5 (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) years, and the median gestational age was 40 (39)(40)(41)(42) weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For metabolomic parameters, inclusion and exclusion criteria were adapted from Rambaud et al [ 23 ] for use with MDD. The keywords used for the search were: (“depression” OR “major depression” OR “major depressive disorder” OR “major depressive episode”) AND (“antioxidant” OR “oxidative stress”).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the brain is more vulnerable to oxidative stress due to its high metabolic rate and lower antioxidant levels [ 18 , 21 ]. Therefore, growing evidence shows the involvement of oxidative stress in brain-related diseases, such as Alzheimer’s disease, schizophrenia, and MDD [ 19 , 20 , 23 ].…”
Section: Introductionmentioning
confidence: 99%